Corticosteroid response in children with nephrotic syndrome, Amirkola Children Hospital, 1994-2001 - H Sorkhi (Babol University of Medical Sciences, 2002)
Background and Objective: Nephrotic syndrome (NS) is one of the kidney diseases in children that was with high mortality and morbidity before starting of management with corticosteroid (CS). Of course, some patients are resistant to CS and do not respond to CS. This study was done to evaluate the resistance and responsiveness to CS. Methods: This analytical study was done on all patients with NS disease who admitted in Amirkola children hospital during 1994-2001. These patients were treated with 60 mg/m² of prednisolone for 4 weeks and then response to CS was evaluated. Findings: Among 73 patients, the ratio of female to male was 1.6 to 1 and most of patients were at the 2-8 age group and were involved in winter (P=0.012). 74% of patients responded to CS, but 26% were resistant to CS. The most responsiveness to CS was at the 2-8 age group (89%). There was not a difference between females and males for response to CS. Conclusion: In this study, response to CS in children with NS was the same with those in some areas and different to others but like other studies, children at the 2-8 age group were involved. Therefore, it is recommended that every patient in this age can be treated with CS without using other invasive diagnostic procedure.